Stigma Dan Realita: Diskriminasi Waria Di Lingkungan Masyarakat - Annisa Salsabila Azzahra; Natanael Sitinjak; Febra Anjar Kusuma; Ninda Putri Sherlyana; Susilo Susilo (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Discrimination against transgender women (waria) in society remains a complex and ongoing social issue. The negative stigma attached to waria is often reinforced by social norms, cultural beliefs, and religious perspectives that uphold a binary gender concept. As a result, waria face discrimination in various aspects of life, including within their families, social environments, workplaces, and access to healthcare and education. This study employs a descriptive qualitative method using in-depth interviews and observations to explore the experiences of discrimination faced by waria and the public's perception of their existence. The findings reveal that social stigma significantly contributes to the marginalization of waria, making it difficult for them to obtain decent employment and leading to rejection within their communities. The media also plays a role in reinforcing negative stereotypes, further exacerbating discrimination against waria. The impact of this discrimination includes psychological distress, economic limitations, and an increased risk of physical and verbal violence. Therefore, more inclusive policies, public education on gender diversity, and the media’s role in fostering a more positive image of waria are essential. Through a more humanistic and human rights-based approach, it is hoped that stigma against waria can be reduced, allowing them to live with dignity and gain social acceptance.